Erythematous papules with central hyperkeratosis in two young women: a quiz - Wiedenmayer, Nadine; Göcebe, Deniz; Bertlich, Ines; Toberer, Ferdinand (Acta dermato-venereologica, 2024)
Abstract is missing (Quiz)